(untitled) (Acta Polytechnica CTU Proceedings, 2019)
This contribution deals with the efficiency of electromigration of chlorides used as a repair method for reinforced concrete structures. Experimental studies of accelerated chloride transport tests were performed on samples of concrete without chlorides and with admixed sodium chloride during concreting. Two concrete types from Portland cement characterized with normal and low compressive strengths were studied. The electromigration was applied to penetrate chlorides into the chloride-free sample and for extraction of chlorides from the sample. The effectiveness of the chloride extraction process for rehabilitation of reinforced concrete in terms of lowering the chloride concentration in different concrete types and surface concentration was observed. Electrical extraction was found to be effective for lowering of initial chloride concentration by 15-20% after 24 hours. The decrease in surface concentrations was found in the range of 40-50%. The extraction process was found to be feasible and effective for both concrete types.